If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 112 + -5x = 10x + -22 Reorder the terms: 112 + -5x = -22 + 10x Solving 112 + -5x = -22 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 112 + -5x + -10x = -22 + 10x + -10x Combine like terms: -5x + -10x = -15x 112 + -15x = -22 + 10x + -10x Combine like terms: 10x + -10x = 0 112 + -15x = -22 + 0 112 + -15x = -22 Add '-112' to each side of the equation. 112 + -112 + -15x = -22 + -112 Combine like terms: 112 + -112 = 0 0 + -15x = -22 + -112 -15x = -22 + -112 Combine like terms: -22 + -112 = -134 -15x = -134 Divide each side by '-15'. x = 8.933333333 Simplifying x = 8.933333333
| b+2a+4c=b | | 1/4x+1/3x+5/6=15/4 | | -8-3=12-8x | | 2r^2-2r-1=0 | | 8+5*lnx-22.6=0 | | 14x-14=0 | | 13-10x=127-32x | | 6-10x=57-31x | | 13-10x=17-32x | | b+2a+4c= | | 3x+4(x-6)+3=0 | | 5/x^3(3x^8) | | x+(17x-18)=90 | | 3p+5=11+2p | | 6m^3+54m^2-6m=0 | | 4n-9=5+3n | | .25q+0.10(2q+6)=7.35 | | p+16p-15=0 | | 5(x-1)-2(x+2)=3 | | 5(4-2c)+3(c+9)=12 | | 4x/5-x/1=x/10-6/2 | | x+(7x-18)=90 | | 4x-2=12x-38 | | 3(1x+2)=1/4 | | p(x)=4x^3+6x^2-22x-12 | | 3(x-1)+5(x+1)=18 | | 8+5(s-2t)= | | 2(4)=4x | | 2(2)=4x | | 2(0)=4x | | 35000.00+1680.00x=300440.00 | | 2(-2)=4x |